SETTLEMENT OF FINANCING DEFAULT AT BMT UGT NUSANTARA BATUURIP SUB-BRANCH JEMBER - Muhammad Syarofi; Moh Hamzah; Uliyatul Mua’wwanah; David Rizqi Zaini (IJED: International Journal of Economy Development Research, 2023)
In line with rapid economic progress, in the world of banking. The main function of banking is as a collector and distributor of public funds. BMT UGT Nusantara distributes funds to the community in the form of financing products. The development of financing can cause problems that must be addressed and resolved. The author is interested in researching financing problems that are in accordance with Islamic banking science. The researcher's curiosity at the heart of the problem is the causes of financing problems at BMT UGT Nusantara and what is the solution to solving financing problems at BMT UGT Nusantara. Research Objectives 1. To find out what are the factors of default in financing at BMT UGT Nusantara head of Batuurip Jember. 2 To find out how to resolve defaults in financing at BMT UGT Nusantara head of Batuurip Jember. The approach taken in this research uses qualitative research, with a case study type of research. Data collection techniques using observation, interviews and documentation, to find out directly from the researcher's location how defaults on financing products are resolved at BMT UGT Nusantara Capem Batuurip. This research concludes that the resolution of defaults that occur at BMT UGT Nusantara Capem Batuurip is by being billed regularly once a week, given a time slot/extension of time, given capital back if collateral allows, and finally the sale of collateral or assets that are guaranteed.